KEBIJAKAN RESTRUKTURISASI KREDIT DIMASA PANDEMI COVID 19 TERHADAP NASABAH (STUDY KASUS) PT BANK SUMUT KCP. MANDALA BY PASS, MEDAN DENAI KOTA MEDAN - Siti Dea Nur Halizah Hsb; Adawiyah Nasution (Sekolah Tinggi Pariwisata Mataram, 2022)
Banking has a very important role in the economic activities of the community. However, where the COVID-19 pandemic affects the community's economy, most of them are very difficult to carry out their obligations as customers to the Bank. So it is very difficult for customers to repay the loan. This study aims to find out how the level of customer ability in credit payments during the covid 19 pandemic and the implementation of credit restructuring carried out according to regulations from PT Bank Sumut KCP Mandala By Pass, Medan City Medan. The type of research used by the author is descriptive research with a qualitative approach to the nature of empirical/sociological research. Data collection techniques are based on documents and interviews. The results of the analysis carried out indicate that the implementation of the credit restructuring policy at PT Bank Sumut KCP Mandala By Pass is running in accordance with the regulations and credit restructuring policies, namely by saving through lowering interest rates, extending the term, reducing credit arrears, reducing principal arrears.